Changes in Public Administration and their Impact on the Control System in Ecuador - Subía-Guerra, Jaime (2020)
The purpose of the study is to highlight the main changes that occurred in the Ecuadorian public administration and how they influenced the control system exercised by the Supreme Audit Institution in the period 1977-2017. Analytical and deductive methods were used to verify the adaptability of the control system to the referred historical moments. It describes the models of internal and external control in a period of transition from the Organic Law of Financial Administration and Control to the Organic Law of the General Comptroller of the State. A necessary comparison is made between the results of the changes generated in the period, with the proposal for the creation of the Court of Accounts in Ecuador, which is driving a transformation of the government control system, which responds to the evolution constant of public administration. The results allow to conclude that, although there is a positive evolution in the normative and methodological aspects, the system requires additional improvement strategies, such as the promotion of institutional risk management, the technical strengthening of the staff of the Supreme Audit Institution, and the impulse to the creation of the Court of Accounts.